Honesty on the Streets - A Natural Field Experiment on Newspaper Purchasing - Gerald J. Pruckner; Rupert Sausgruber (University of Innsbruck, Department of Public Finance, 2009)
A publisher uses an honor system for selling a newspaper in the street. The customers are supposed to pay, but they can also pay less than the price or not pay at all. We conduct an experiment to study honesty in this market. The results show that appealing to honesty increases payments, whereas reminding the customers of the legal norm has no effect. Furthermore, appealing to honesty does not affect the behavior of the dishonest. These findings suggest that some people have internalized an honesty norm, whereas others have not, and that the willingness to pay to obey the norm differs among individuals. In a follow-up survey study we find that honesty is associated with family characteristics, self-esteem, social connectedness, trust in the legal system, and compliance with tax regulations.
Keywords: C93; K42; 330; honesty; internalized social norm; natural field experiment; survey; Zeitung; Konsumentenverhalten; Soziale Norm; Test